PENGEMBANGAN PERANGKAT PEMBELAJARAN KONSTRUKTIVISME MENGGUNAKAN MODEL KOOPERATIF DI KELAS 5 SEKOLAH DASAR - Asmar, Ali (Universitas PGRI Sumatera Barat, 2017)
Based on a pre-observation and interview on the Mathematics Padang Panjang teachers, it was found that the instructional materials they used have not yet facilitate the students to construct their own learning in Mathematics. The purposes of this research were to develop a Constructivism learning materials for 5th Grade Elementary School students in Padang Panjang, consisted of lesson plan, hand out, and student worksheet. The learning materials were developed use models Cooperative Learning. This research was a combination of Research and Development (R & D) and Experimental. Based on the data analysis, the findings of this research were: (1) The Cooperative instructional materials for 5th Grade Mathematics was found “valid” for its content and construct (content and construct validity). (2) The Cooperative instructional materials which had been developed fulfill the practicality and that it can be easily used by the teachers without any difficulty. The conclusion of this research is that the Constructivism-based instructional materials with cooperative learning model are: (1) Generated, Hand - outs are valid and meet the requirements of teaching materials is good, (2) LKS in the category is valid , and can be used with minor revisions, (3) RPP compiled in the category is valid and can be used with minor revisions, (4) Prototype handouts , worksheets , and lesson plans produced has good practicalities.